Hydatid cyst presenting as a soft-tissue calf mass in a child - EROL, BÜLENT (GEORG THIEME VERLAG KG, 2007)
Hydatid disease caused by Echinococcus granulosus often manifests as a slow growing cystic mass; it mainly affects the liver or lung and rarely other parts of the body such as the brain, heart, spleen, peritoneal cavity, or bone. Hydatid cysts of the musculoskeletal system are rare. Since the intramuscular hydatid cyst closely resembles a soft-tissue tumor on clinical examination, the preoperative radiological diagnosis is very important for the identification of the lesion prior to surgery. We describe a rare case of primary intramuscular hydatidosis in a child, together with its clinical presentation and radiological and histological findings. The treatment principles for hydatid cysts are also discussed.
Keywords: hydatid cyst; intramuscular; surgical excision; PRIMARY INTRAMUSCULAR HYDATIDOSIS; DISEASE; MUSCLE; LIVER